Intimate Partner Violence against Men in Cali, Colombia (2016)
Purpose: In Colombia, intimate partner violence is a public health problem that has a significant impact on society. Therefore, the purpose of this article is to characterize intimate partner violence against men in cases that occurred in Cali in 2014 and were evaluated at the Southwestern Regional Office of the Institute of Legal Medicine. Description: A descriptive study was conducted and 78 cases were found and reviewed one by one; a mean age of 33 years was determined, the most affected group being young adults (88%) with common law marriage as the most frequent marital status (58%). The months with more cases were December, October and February (39%), without a clear relation with national festivities; and the predominant days were weekends (49%). Approach: It was striking that 45% of the events took place during non-business hours. The main triggering cause was intolerance (63%), and previous abuse was reported in 74% of the assessments. Conclusions: This study allows the characterization of a poorly described phenomenon that requires additional studies to evaluate patterns of violence, triggers or risk factors, etc., without neglecting the true focus and assistance that should be provided to all victims of violence, regardless of gender, and ensuring the fulfillment of their rights and the launch of new primary prevention programs.